2022
DOI: 10.3390/buildings12081273
|View full text |Cite
|
Sign up to set email alerts
|

Use of Industrial Silica Sand as a Fine Aggregate in Concrete—An Explorative Study

Abstract: Industrial silica sand is a by-product obtained from the industries like paint, paper, rubber etc. It has a similar property with river sand and& M sand. This study explores the effect of high content of silica sand as a partial replacement for fine aggregate for concrete making in construction purpose. In this present research four types of silica sand from two different industrial units (coarser silica sand (VC and TC) and finer silica sand (VF and TF)) were used. The physical classification and morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Finally, it was found that the compressive strength was 0.1 MPa. The sand particles were very fine, which resulted in a decrease in the mechanical properties [27][28][29]. The sand silica density was estimated to be around 2059 kg/cm 3 [30,31].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, it was found that the compressive strength was 0.1 MPa. The sand particles were very fine, which resulted in a decrease in the mechanical properties [27][28][29]. The sand silica density was estimated to be around 2059 kg/cm 3 [30,31].…”
Section: Methodsmentioning
confidence: 99%
“…The scale range used in the SEM analysis was 5 µm with the resolution of 5000x. The samples were examined in the SEM instrument [ 46 , 47 , 48 , 49 , 50 ]. After the flexural strength test, mortar bonded with the fabrics was taken out from the ferrocement composites.…”
Section: Methodsmentioning
confidence: 99%
“…Natural minerals can also be transformed into basic materials (Kenzhaliyev et al, 2022). Sand as Concrete Fine Aggregate (Malathy et al, 2022). From previous research, To maximize natural products, preliminary research is required to convert sand into high-value minerals, thereby enhancing the economic value of the people in the Talang Siring beach region.…”
Section: Figure 1 Map Of Pamekasan Madura Regencymentioning
confidence: 99%